Deployment of Optimized Algorithm for MPEG-4 Data Over Wireless Multimedia Sensor Network - Hashim, Norlezah; Idris, Fakrulradzi; Syed Ariffin, Dr Sharifah Hafizah; Yunus, Farizah; Fisal, Norsheila (2006-2014 Asian Research Publishing Network (ARPN), 2014)
Typical Wireless Sensor Network (WSN) always deals with scalar data such as temperature. These types of data are suitable for low rate networking technology such as IEEE802.15.4. Transmitting a video for IEEE 802.15.4 raised other challenges for bandwidth limited sensor networks like WSN. The optimization method able to determine the optimal limit for quantization scale, group of picture and frame per second in order to suit the WSN environment. Changing these parameters affects the bandwidth requirement and video quality in term of Peak Signal to Noise Ratio (PSNR). This project aims to create an embedded code in TelG mote according to this concept. Results from experiment show improvements in packet delivery ratio of 28% for Akiyo qcif file, 27% for Foreman qcif file and 9% for Mobile qcif file. This work proved that the method has successfully increased the network performance.